Sprawność narracyjna w chorobie alkoholowej - Ciszewska-Psujek, Urszula (Logopedia Silesiana, 2017)
Narrative Abilities in Alcohol Use Disorder Alcohol dependence is a chronic disease causing multiple‑system and multiorgan damage. Toxic effects of alcohol on the central nervous system lead to a permanent decrease in the number and size of neurons and neuronal connections, especially in the frontal structures, limbic system and cerebellum, and consequently to cognitive disorders, including executive functions and memory, as well as disorders in the processing of emotional information. The resulting cognitive dysfunctions affect the way in which reality is understood and the ability to present it in linguistic behaviour. Speech disorders in alcohol addicts can be diagnosed by assessing the narrative skills that reflect human knowledge of the world, i.e. the cognitive representation of the world. Key words: alcoholism, cognitive functions, executive functions, cognitive function disorders, narration, narrative efficiency